Concerning the structure of apoE. (19th October 2013) - Frieden, Carl; Garai, Kanchan
Abstract: Apolipoprotein E (apoE), first described in 1973, is a truly fascinating protein. While studies initially focused on its role in cholesterol and lipid metabolism, one apoE isoform (apoE4) is a major risk factor for development of late onset Alzheimer's disease. Yet the difference between apoE3, the common form, and apoE4 is a single amino acid of the 299 in this 34 kDa protein. Structure determination of the two domain full length apoE3 protein was only accomplished in 2011 and supports the notion that mutations in the N‐terminal domain can be propagated through the structure to the C‐terminal domain. Understanding the structural differences between apoE3 and apoE4 is critical for finding ways to modulate the deleterious effect of apoE4.